2003
DOI: 10.1093/nar/gkg437
|View full text |Cite
|
Sign up to set email alerts
|

The C terminus of the human telomerase reverse transcriptase is a determinant of enzyme processivity

Abstract: The catalytic subunit of telomerase (TERT) contains conserved reverse transcriptase-like motifs but N- and C-terminal regions unique to telomerases. Despite weak sequence conservation, the C terminus of TERTs from various organisms has been implicated in telomerase-specific functions, including telomerase activity, functional multimerization with other TERT molecules, enzyme processivity and telomere length maintenance. We studied hTERT proteins containing small C-terminal deletions or substitutions to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
125
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 62 publications
6
125
0
1
Order By: Relevance
“…The C-terminal domain also contains sequences conserved among TERT proteins from divergent species (7,32,56). In S. cerevisiae, the C-terminal domain modulates telomerase processivity, although TERT mutants in which this domain is entirely deleted retain enzymatic function and the corresponding mutant yeast strains remain viable (31,56).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The C-terminal domain also contains sequences conserved among TERT proteins from divergent species (7,32,56). In S. cerevisiae, the C-terminal domain modulates telomerase processivity, although TERT mutants in which this domain is entirely deleted retain enzymatic function and the corresponding mutant yeast strains remain viable (31,56).…”
mentioning
confidence: 99%
“…In contrast, C-terminal deletions in hTERT abrogate telomerase activity, indicating that this region is necessary for catalytic function (5,8). Similarly, the deletion or mutation of conserved residues in the C-terminal domain of hTERT impairs telomerase processivity (32). The fact that TERT enzymatic function in vitro is sensitive to both N-and C-terminal deletion analysis has complicated efforts to understand TERT function in vivo through the identification of protein domains that control immortalization or telomere maintenance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A, lanes 1 and 2). Low levels of DNA synthesis that can be difficult to detect using the direct primer extension assay can sometimes be more readily detected using the sensitive PCR-based telomerase assay (TRAP) [17,40]. For instance, though we failed to detect substantial elongation by the chTR/chTERT (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Studies have demonstrated that the human telomerase enzyme is one of the most processive telomerase complexes, especially compared to the murine one [10,11]. Human telomerase processivity is mediated by template and nontemplate regions of human TR (hTR) and by regions in human TERT (hTERT), specifically the C-terminal and N-terminal RNA interaction domain 1 [12][13][14][15][16][17]. The ectopic expression of hTERT enables the immortalization not only of human primary cells, but also of other primary vertebrate cells such as leporine, bovine, porcine, simian and cervine cells [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%